Carrier free co-immobilization of alpha amylase, glucoamylase and pullulanase as combined cross-linked enzyme aggregates (combi-CLEAs): a tri-enzyme biocatalyst with one pot starch hydrolytic activity - Talekar, Sachin; Pandharbale, Amol; Ladole, Mayur; Nadar, Shamraja; Mulla, Mosin; Japhalekar, Kshitija; Pattankude, Kishori; Arage, Devika (Bioresource Technology, 2013)
A tri-enzyme biocatalyst ``combi-CLEAs'' with starch hydrolytic activity was prepared from commercially available alpha amylase, glucoamylase and pullulanase preparations by aggregating enzymes with ammonium sulphate followed by cross-linking formed aggregates for 4.5 h with 40 mM glutaraldehyde. The effects of precipitant type and cross-linking were studied and the biocatalyst was characterized. Scanning electron microscopy analysis showed that tri-enzyme biocatalyst was of spherical structure. For one pot starch hydrolytic activity, shift in optimum pH from 6 to 7 and temperature from 65 to 75 degrees C were observed after co-immobilization of enzymes. After one pot starch hydrolysis reaction in batch mode, 100%, 60% and 40% conversions were obtained with combi-CLEAs, separate CLEAs mixture and free enzyme mixture, respectively. Co-immobilization also enhanced the thermal stability of enzymes. Finally, the catalytic activity of enzymes in combi-CLEAs during one pot starch hydrolysis was well maintained up to five cycles without performance changes. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Alpha amylase; Combined cross-linked enzyme aggregates (combi-CLEAs); Glucoamylase; One pot starch hydrolysis; Pullulanase